Measurement properties of quality‐of‐life measurement instruments for infants, children and adolescents with eczema: a systematic review - Heinl, Daniel; Ofenloch, Robert (British journal of dermatology, 2017)
Background: Quality of life (QoL) is one of the core outcome domains identified by the Harmonising Outcome Measures for Eczema (HOME) initiative to be assessed in every eczema trial. There is uncertainty about the most appropriate QoL instrument to measure this domain in infants, children and adolescents. Objectives: To systematically evaluate the measurement properties of existing measurement instruments developed and/or validated for the measurement of QoL in infants, children and adolescents with eczema. Methods: A systematic literature search in PubMed and Embase, complemented by a thorough hand search of reference lists, retrieved studies on measurement properties of eczema QoL instruments for infants, children and adolescents. For all eligible studies, we judged the adequacy of the measurement properties and the methodological study quality with the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) checklist. Results from different studies were summarized in a best-evidence synthesis and formed the basis to assign four degrees of recommendation. Results: Seventeen articles, three of which were found by hand search, were included. These 17 articles reported on 24 instruments. No instrument can be recommended for use in all eczema trials because none fulfilled all required adequacy criteria. With adequate internal consistency, reliability and hypothesis testing, the U.S. version of the Childhood Atopic Dermatitis Impact Scale (CADIS), a proxy-reported instrument, has the potential to be recommended depending on the results of further validation studies. All other instruments, including all self-reported ones, lacked significant validation data. Conclusions: Currently, no QoL instrument for infants, children and adolescents with eczema can be highly recommended. Future validation research should primarily focus on the CADIS, but also attempt to broaden the evidence base for the validity of self-reported instruments.